Analisis Perencanaan Persediaan Air Mineral dengan Pendekatan Metode Monte Carlo pada PT. Agrimitra Utama Persada - Dedrizaldi Dedrizaldi; Erni Masdupi; Muthia Roza Linda (Jurnal Kajian Manajemen dan Wirausaha, 2019)
This study aims to determine how the planning of finished goods inventory at PT. Agrimitra Utama Persada using Monte Carlo Simulation which is useful in carrying out repeated experiments from existing data. So that the repeated experiment will produce a pattern that is expected to be used to manage inventory. In this study, we will discuss forecasting using the Naive Method, exponential smoothing, Weighted Moving Average, and Moving Average and for inventory planning using Monte Carlo Simulation calculations. The research methodology used is a quantitative method. The type of data used in this study is secondary data. From the calculations obtained the best method of forecasting calculations based on MAPE, MAD and MSE is the smallest, namely the Naive method because the results of the forecasting error are the smallest for bottled water products (AMDK). The values of MAPE, MAD and MSE from the Naive Method are MAPE of 12.29%, MAD of 28607, and MSE of 1366039931. Results of Monte Carlo Simulation can be determined for the number of requests in 2018 of 2,669,458 boxes and average demand in one week of 5448.73 cardboard boxes. Keywords : Inventory, Forecasting, Simulasi Monte Carlo